2015
DOI: 10.1016/j.ijmachtools.2015.09.006
|View full text |Cite
|
Sign up to set email alerts
|

The linear inverse problem in energy beam processing with an application to abrasive waterjet machining

Abstract: a b s t r a c tThe linear inverse problem for energy beam processing, in which a desired etched profile is known and a trajectory of the beam that will create it must be found, is studied in this paper. As an example, abrasive waterjet machining (AWJM) is considered here supported by extensive experimental investigations. The behaviour of this process can be described using a linear model when the angle between the jet and the surface is approximately constant during the process, as occurs for shallow etched p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 18 publications
(25 reference statements)
0
24
0
Order By: Relevance
“…The model is computationally inexpensive, taking less than 10 seconds to simulate the processing of one mm 2 surface, and accurate, less than 5% error on average; it can be used as a tool to pre-compute and optimise the beam path and also as an online prediction tool in association with inline measurement systems. It represents a significant development in pulsed laser machining and allows the development of specialised CAD/CAM software for the automatic planning and optimisation of the beam path and processing parameters as presented for abrasive waterjet machining in [36].…”
Section: Resultsmentioning
confidence: 99%
“…The model is computationally inexpensive, taking less than 10 seconds to simulate the processing of one mm 2 surface, and accurate, less than 5% error on average; it can be used as a tool to pre-compute and optimise the beam path and also as an online prediction tool in association with inline measurement systems. It represents a significant development in pulsed laser machining and allows the development of specialised CAD/CAM software for the automatic planning and optimisation of the beam path and processing parameters as presented for abrasive waterjet machining in [36].…”
Section: Resultsmentioning
confidence: 99%
“…It has been found that, for shallow trenches (i.e. large feed speeds), a linear model can be used to predict the average trench profile [22], and therefore the problem can be stated as…”
Section: Stochastic Modelling Of Abrasive Waterjet Millingmentioning
confidence: 99%
“…This is preferable to an ordinary jet sample on the material effect through the positive impact of broken rock. So rotating conical abrasive jet pressure on the material radial is in the form of an "extend" force and a circular "cut" force, plus the positive impact force, and it will be easy to meet or exceed the corresponding strength of the materials, which produces material destruction through stretch and shear, greatly improving the crushing efficiency [17] [18].…”
Section: Track Equation Of the Rotating Water Jetmentioning
confidence: 99%